Sex and ageing differences in resting arterial pressure regulation: the role of the β-adrenergic receptors - Hart, Emma C (Blackwell Science Inc, 2011)
ABSTRACT: In men, muscle sympathetic nerve activity (MSNA) is positively related to total peripheral resistance (TPR) and inversely related to cardiac output (CO). However, this relationship was not observed in young women. We aimed to investigate whether simultaneous β-adrenergic stimulation offsets this balance in young women. Furthermore, we aimed to examine whether the ability of the β-adrenergic receptors to offset the transduction of MSNA into vasoconstrictor tone was lost in postmenopausal women. We measured MSNA (peroneal microneurography), arterial pressure (brachial line), CO (Modelflow), TPR and changes in forearm vascular conductance (FVC) to increasing doses of noradrenaline (NA; 2, 4 and 8 ng (100 ml)(−1) min(−1)) before and after systemic β-blockade with propranolol in 17 young men, 17 young women and 15 postmenopausal (PM) women. The percentage and absolute change in FVC to the last two doses of NA were greater during β-blockade in young women (P < 0.05), whereas the change in FVC was similar before and during β-blockade in young men and PM women (P > 0.05). Before β-blockade there was no relationship of MSNA to TPR or mean arterial pressure (MAP) in young women. Following β-blockade, MSNA became positively related to TPR (r = 0.59, P < 0.05) and MAP (r = 0.58, P < 0.05). In the PM women and young men, MSNA was positively associated with TPR. β-Blockade had no effect on this relationship. Our data suggest that the β-adrenergic receptors offset α-adrenergic vasoconstriction in young women but not young men or PM women. These findings may explain in part the tendency for blood pressure to rise after menopause in women.